Job satisfaction as a mediator between leadership styles and organisational commitment of teachers in Malaysia / Norhaily Abdul Halim ... [et al.] - Abdul Halim, Norhaily; Hassan, Aminuddin; Basri, Ramli; Yusof, Aminuddin; Ahrari, Seyedali (Universiti Teknologi MARA, 2021)
To better understand the organisational commitment of teachers, the current study examined job satisfaction as a mediator between organisational commitment and the three dimensions of leadership, namely transformational, transactional and passive-avoidant. The study involved 381 school teachers in Malaysia, and the multiple-model analysis used showed partial mediation on the negative association of passive-avoidant leadership style with teachers' commitment to their organisation. The study found a relationship between transformational leadership and organisational commitment through job satisfaction. As expected, job satisfaction also fully mediated between transaction leadership and organisational commitment among teachers, and that teachers who are highly satisfied with their jobs attributed their commitment towards their school to transaction leadership. This study extends the knowledge on the effects of teachers' leadership styles on their organisational commitments through a mediating factor. Higher education can play an important role in changing pre-service teachers' and future school principals' mindsets to exhibit transformation and transaction leadership competencies. Therefore, leadership development and training of future school administrators during their tertiary education are important in order to enhance teachers' job satisfaction and commitment.